2019
DOI: 10.1016/j.cois.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The defensive Spiroplasma

Abstract: Defensive microbes are of great interest for their roles in arthropod health, disease transmission, and biocontrol efforts. Obligate bacterial passengers of arthropods, such as Spiroplasma, confer protection against the natural enemies of their hosts to improve their own fitness. Although known for less than a decade, Spiroplasma's defensive reach extends to diverse parasites, both microbial and multicellular. We provide an overview of known defensive phenotypes against nematodes, parasitoid wasps, and fungi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 53 publications
1
60
0
Order By: Relevance
“…Moreover, we have shown that, in Aedes aegypti , these RIP genes are transcribed and their expression levels are modulated across the developmental stages 15 . Recently, evidence has been accumulated on the role of Spiroplasma spp RIPs in the protective mechanisms generated by these endosymbiotic species against arthropod infection by natural enemies (see 16 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have shown that, in Aedes aegypti , these RIP genes are transcribed and their expression levels are modulated across the developmental stages 15 . Recently, evidence has been accumulated on the role of Spiroplasma spp RIPs in the protective mechanisms generated by these endosymbiotic species against arthropod infection by natural enemies (see 16 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…). Similar to other heritable endosymbionts, some Spiroplasma have evolved the ability to defend their hosts against other infections (Ballinger and Perlman ). For example, the male killing strain MSRO of S. poulsonii protects Drosophila melanogaster against parasitoid wasps (Xie et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that between 5% and 10% of insects carry heritable infections with Spiroplasma (Duron et al 2008). Similar to other heritable endosymbionts, some Spiroplasma have evolved the ability to defend their hosts against other infections (Ballinger and Perlman 2018). For example, the male killing strain MSRO of S. poulsonii protects Drosophila melanogaster against parasitoid wasps (Xie et al 2014;Paredes et al 2016), illustrating that reproductive manipulation and protection are not mutually exclusive strategies of symbionts to spread in host populations.…”
Section: Introductionmentioning
confidence: 99%
“…Our research also evidenced that these genes are derived from a single HGT event from a bacterial donor species [14]. Recently, evidence has been accumulated on the role of Spiroplasma spp RIPs in the protective mechanisms generated by these endosymbiotic species against arthropod infection by natural enemies (see [15] for a review).…”
Section: Introductionmentioning
confidence: 53%